Congenital cytomegalovirus infection in newborns suspected of congenital rubella syndrome in Iran: a cross-sectional study - Negar Mirsalehi; Jila Yavarian; Nastaran Ghavami; Maryam Naseri; Farshad Khodakhah; Somayeh Shatizadeh Malekshahi; Sevrin Zadheidar; Talat Mokhtari-Azad; Nazanin-Zahra S (BMC, 2024)
Abstract Background Following rubella virus control, the most important cause of congenital infections is human cytomegalovirus (HCMV). Congenital CMV (cCMV) may happen both in primary and non-primary maternal infections. The present study aimed to screen cCMV in symptomatic newborns suspected of congenital rubella syndrome (CRS) in Iran. Methods Out of 1629 collected infants' serum samples suspected of CRS but negative for rubella IgM, 524 samples were selected regarding cCMV complications. These samples were divided into two age groups: 1- one month and younger, 2- older than 1 month up to one year. Anti-HCMV IgM detection was performed on these serums. Then HCMV IgG avidity assay and HCMV DNA detection were carried out on all samples with positive and borderline results in IgM detection. Results Herein, 3.67% of symptomatic infants aged one month and younger had positive and borderline HCMV IgM, 12.5% of which had a low avidity index (AI). HCMV IgM detection rate among symptomatic infants older than one month to one year was 14.5%. Identified genotypes in this study were gB-1(63.63%), gB2 (18.18%), and gB3 (18.18%), respectively. Conclusions This comprehensive study was performed on serum samples of symptomatic infants clinically suspected of cCMV from all over Iran. There was a good correlation between serology findings and PCR.